Planning technology one seat at a time. - Jarvis, Daniel (American City & County, 2002)
A seat management program can be established by local governments to manage equipment inventory. Seat management involves distributing and tracking all items used at employees' workstations, including office supplies and software, access cards for doors, and passwords for computer security. Such a formal system can save local governments time and money as well as allowing them to better forecast and track their costs for activities related to hiring and relocating employees. The seat management program in place in Denver is described.